Characteristics of natural wind - Pt. I: Mean flow - SHARAN, V. KR. (MAUSAM, 1975)
The aerodynamic friction offered by various objects on the earth and the earth itself to the movement of air creates wind forces on structures. These wind forces have become more and more critical due to the more slender and unusual design of present day structures. The available data on mean wind speed measurement in the lower part of the atmospheric boundary layer, as relevant to wind loading on structures, are analysed critically and correlated analytically. It is concluded that under certain conditions the variation of mean wind speed with height ill neutral stability can be satisfactorily represent6d by a simple power law. The index of the power law and the corresponding gradi6llt height must, however, be varied to take account of the roughness of the surface. Further the total change in mean wind direction over a few hundred feet being a few degrees, may be neglected during considerations of most structures. Finally suggestions are made for the power law exponent, gradient height and the surface drag coefficient for the four typical categories of terrain. The suggested values are confirmed by recent measurements of wind speed made in various parts of the world.